Participatory Crop Improvement of Nepalese Fingermillet Cultivars - Bajracharya, Sharad; Prasad, Ram C.; Budhathoki, Shiva K. (Nepal Agriculture Research Journal, 2014)
A field study was undertaken on Nepalese fingermillet genotypes with the participation of the local community at pipaltar of nuwakot district during 2003 and 2004. The study included a) identification of superior fingermillet cultivars through diversity block management and mother set trial, b) seed Production of promising lines, c) farmers' field verification trial (diamond trial) And d) characterization and documentation of fingermillet genotypes. Results Revealed that mudke, chaure and jalbire are high yielding promising genotypes Suited to that area. From household surveys carried out among 46 samples (40%), 80 hh have revealed that mudke, chaure and seto kodo are preferred fingermillet cultivars. About 70% grow mudke, 46% grow chaure while 2% Grow Seto Kodo. The programme has successfully explored the potential of Local fingermillet cultivars by there evaluation and utilized them through Value added product development and market promotion. Nepal Agric. Res. J. Vol. 9, 2009, pp. 12-16 DOI: http://dx.doi.org/10.3126/narj.v9i0.11636